Re-registration Challenges of Glyphosate in the European Union - Székács, András; Darvas, Béla (Frontiers in Environmental Science, 2018)
One of the most controversial societal issues today, regarding pesticide registration in the European Union (EU) may be the case surrounding re-registration of the active herbicide ingredient glyphosate. Shortly before the announcement of the conflicting views regarding the carcinogenicity status of this regulated agrochemical by EU Agencies, the European Food Safety Authority (EFSA) and the European Chemicals Agency (ECHA) on the one hand, and the International Agency for Research on Cancer (IARC) on the other hand, the Cancer Assessment Review Committee of the US Environmental Protection Agency (US EPA) also published re-evaluations. The US EPA assessment classified glyphosate into Group E, “not likely to be carcinogenic to humans”. Similar positions were reached by EFSA and ECHA, assessing glyphosate as “unlikely to pose a carcinogenic hazard to humans” and “not classified as a carcinogen”, respectively. A strongly opposing evaluation has previously been reached by IARC by classifying glyphosate into Group 2A, “probably carcinogenic to humans”. IARC identified potential cancer hazards in this case, but did not estimate the level of risk it may present, which was taken into consideration by opposing agencies. Multiple effects of glyphosate have been reported, of which carcinogenic effects are only one component. Formulated glyphosate products – especially with polyethoxylated tallowamine and related compounds – have been shown to cause stronger cytotoxic or endocrine disrupting effects than the active ingredient glyphosate alone. Questions related to hazards and corresponding risks identified in relation to this active ingredient and its formulated herbicide preparations divide scientific circles and official health and environmental authorities and organizations, and touch upon fundamental aspects of risk assessment and product regulation. The decision has to consider both hazard-based (IARC) and risk-based analysis (EFSA); the former may not be suitable to calculate practical significances, and the latter being challenged if exposure estimations are uncertain in light of new data on residue levels. The results of current analytical surveys on surface water are particularly worrisome. In turn, the precautionary principle appears to be the optimal approach in this case for regulation in the EU.